Social work field education in Vietnam: Challenges and recommendations for a better model. (November 2022) - Nguyen, Hoa Thi; Cohen, Edward; Văn Đỗ, Toản; Nguyễn, Diễm Hương Thùy; Ngô, Thanh Mai Thi; Văn Kiều, Tu; Thị, Kim Dung Lê; Đặng, Minh Lý Thị; Le, Thuy Thi; Bùi, Minh Thanh
Given the rapid expansion in social work education, universities in Vietnam are facing tremendous challenges in organizing effective field practicum. This article explores the current field practicum models in Vietnam, its strengths, challenges and recommendations for enhancement. The study utilized a case-study approach in which focus groups and in-depth interviews were conducted. The key strengths included diverse and comprehensive content, and enthusiasm and support from field supervisors and instructors. The key challenges were lack of qualified field supervisors, loose collaboration between universities and field agencies, and inadequate student assessment methods. Specific recommendations are presented that fit the contexts of Vietnam.